Graphitization treatment method of calcined petroleum coke

By pelletizing and molten salt electrolysis on the calcined petroleum coke, the problems of high energy consumption and serious environmental pollution of calcined petroleum coke are solved, efficient and low-cost graphitization effect are achieved, and graphitization degree and sulfur resources are improved.

CN119553289AActive Publication Date: 2025-03-04CHINALCO RES INST OF SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510126678.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-03-04
Estimated Expiration
2045-01-27

AI Technical Summary

Technical Problem

In the prior art, the energy consumption and cost of graphitization of petroleum coke after calcination is high, the environmental pollution is serious, the raw materials are required, and the technical limitations are obvious.

Method used

After the calcined petroleum coke is used for sphere formation, the cathode and anode of the petroleum coke are electrolyzed by molten salt electrolysis to obtain graphitized petroleum coke. The method includes steps such as grinding, spray-drying sphere formation, current collector wrapping, molten salt water removal and pre-electrolysis.

Benefits of technology

It effectively reduces graphitization temperature, reduces energy consumption and costs, improves environmental friendliness, and improves graphitization degree, while achieving efficient recycling and utilization of sulfur resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553289A_ABST
    Figure CN119553289A_ABST
Patent Text Reader

Abstract

The invention provides a graphitization treatment method of calcined petroleum coke. The calcined petroleum coke is obtained by distilling and thermally cracking crude oil, and the graphitization treatment method comprises the following steps: S1, pelletizing the calcined petroleum coke to obtain a petroleum coke cathode; and S2, the petroleum coke cathode and the petroleum coke anode are subjected to molten salt electrolysis, and the graphitized petroleum coke is obtained. According to the method, the low-graphitization calcined petroleum coke is converted into the high-graphitization-degree carbon material graphitized petroleum coke through the molten salt electrolysis graphitization method, and compared with a traditional graphitization method, the graphitization temperature can be effectively reduced by adopting an electrochemical method, so that the graphitization energy consumption and cost are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphitization treatment, in particular to a graphitization treatment method for calcined petroleum coke. Background Art

[0002] In the aluminum electrolysis industry, calcined petroleum coke is the key raw material for prebaked anodes and graphitized cathode carbon blocks. Its graphitization degree directly affects the efficiency and production cost of aluminum electrolysis. Graphitization is an effective way to change the structure of carbonaceous materials to make them have properties such as high temperature resistance, electrical conductivity and chemical stability. The traditional graphitization process needs to be carried out at high temperatures (usually close to 3000℃), which not only consumes a lot of electricity, but also has dangerous production conditions and produces a lot of pollutants.

[0003] At present, the main methods to improve graphitization include catalytic graphite method and high temperature and high pressure method. However, a large amount of catalyst is used in the catalytic graphite method, which is difficult to remove from the graphite; the high temperature and high pressure method is difficult to achieve graphitization for porous chaotic layer carbon materials. The main problems currently faced by the graphitization process of petroleum coke after aluminum electrolytic calcination include high energy consumption and cost, serious environmental pollution, large fluctuations in raw material quality, obvious technical limitations and increased resource consumption. These problems not only lead to high production costs and serious environmental pollution, but also affect the quality of the final product. Therefore, it is necessary to develop a new type of graphitization technology. Summary of the invention

[0004] The main purpose of the present invention is to provide a graphitization treatment method for calcined petroleum coke to solve the problems of high energy consumption and cost, great environmental pollution and high requirements for raw materials in the prior art of graphitization of calcined petroleum coke.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for graphitizing calcined petroleum coke is provided, wherein the calcined petroleum coke is obtained from crude oil by distillation and thermal cracking, and the method for graphitizing comprises: step S1, pelletizing the calcined petroleum coke to obtain a petroleum coke cathode; and step S2, subjecting the petroleum coke cathode and anode to molten salt electrolysis to obtain graphitized petroleum coke.

[0006] Furthermore, the calcined petroleum coke comprises, by mass percentage, 90-93% carbon, 0.5-1% oxygen, 1-4% sulfur, 0.5-1% nitrogen, and the remainder other impurity elements; and / or the graphitization degree of the graphitized petroleum coke is 40-65%.

[0007] Furthermore, the above step S1 also includes: step S11, grinding the calcined petroleum coke to obtain petroleum coke powder; step S12, pelletizing the petroleum coke powder by spray drying to obtain petroleum coke microspheres; and step S13, wrapping the petroleum coke microspheres with a current collector to obtain a petroleum coke cathode.

[0008] Furthermore, the particle size of the petroleum coke powder is 1-100 nm; and / or the diameter of the spray-dried droplets is 20-100 μm, and / or the spray-drying time is 5-10 s; and / or the diameter of the petroleum coke microspheres is 5-10 μm; the current collector is selected from any one or more of metal mesh, metal foam, graphite paper, graphite mesh and graphite column.

[0009] Furthermore, the above step S2 also includes removing moisture and pre-electrolyzing the molten salt in sequence to obtain treated molten salt.

[0010] Furthermore, the molten salt is evacuated at 180-240° C. in a vacuum environment to remove moisture, and the evacuation time is 16-48 hours.

[0011] Further, the molten salt is pre-electrolyzed after the water is removed after the temperature is raised to 900-950° C. under an argon atmosphere; and / or the voltage of the pre-electrolysis is 1.5-2V, and / or the time of the pre-electrolysis is 1.5-3h.

[0012] Furthermore, the molten salt is selected from eutectic molten salt and / or fluoride, the eutectic molten salt is selected from any one or more of CaCl2-LiCl, CaCl2-NaCl, CaCl2-BaCl2 and CaCl2-KCl, and the fluoride is selected from any one or more of NaF, CaF2, BaF2 and KF.

[0013] Furthermore, the above step S2 also includes: step S21, placing the cathode and anode of the petroleum coke in the treated molten salt in an inert atmosphere for molten salt electrolysis to obtain electrolyzed petroleum coke; and step S22, washing, acid washing and drying the electrolyzed petroleum coke in sequence to obtain graphitized petroleum coke.

[0014] Furthermore, the inert atmosphere is argon or nitrogen; and / or, the anode is graphite; and / or, the temperature of molten salt electrolysis is 850~980℃, and / or, the voltage of molten salt electrolysis is 2.6~3.1V, and / or, the time of molten salt electrolysis is 2~10h; and / or, ultrasonic-assisted distilled water is used for water washing; and / or, acid solution is used for pickling, and the acid solution is a hydrochloric acid solution with a mass concentration of 1~10%; and / or, the drying temperature is 70~80℃.

[0015] Applying the technical solution of the present invention, the present application converts low-graphitization calcined petroleum coke into graphitized petroleum coke, a carbonaceous material with a high degree of graphitization, through a molten salt electrolytic graphitization method. Compared with traditional graphitization methods, the use of an electrochemical method can effectively reduce the graphitization temperature, thereby reducing the energy consumption and cost of graphitization. Specifically, in step S1, the calcined petroleum coke is subjected to a pelletizing treatment, which can effectively improve the structural stability of the calcined petroleum coke and the conductivity between the calcined petroleum coke and the electrolyte molten salt. Among them, the pelletizing treatment is to make the raw material into a spherical material with a certain shape and strength. In step S2, during the electrolysis process, the molten salt can not only transmit current and provide an environment for the electrolytic reaction, but also promote the orderly arrangement of carbon atoms in the calcined petroleum coke and the formation of a graphite structure through its unique ionic effect and chemical properties. Specifically, the molten salt electrolysis method can not only effectively remove gas element impurities (such as oxygen, sulfur and nitrogen, etc.) in the petroleum coke cathode, but also effectively remove a large amount of sulfur content in the petroleum coke cathode, and at the same time make the removed sulfur ions form sulfur on the surface of the anode, thereby realizing efficient recycling of sulfur resources and reducing the consumption of the anode. In addition, the processing method of the present application has low requirements on the quality of raw materials and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0017] Figure 1 The XRD pattern of graphitized petroleum coke in Example 1 of the present application is shown. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0019] As analyzed in the background technology of this application, the existing technology has the problems of high energy consumption and cost, great environmental pollution and high requirements for raw materials for graphitization of calcined petroleum coke. In order to solve the above problems, this application provides a method for graphitization of calcined petroleum coke.

[0020] In a typical embodiment of the present application, a method for graphitizing calcined petroleum coke is provided. The calcined petroleum coke is obtained from crude oil by distillation and thermal cracking. The method for graphitizing comprises: step S1, pelletizing the calcined petroleum coke to obtain a petroleum coke cathode; and step S2, subjecting the petroleum coke cathode and anode to molten salt electrolysis to obtain graphitized petroleum coke.

[0021] The present application converts low-graphitization calcined petroleum coke into graphitized petroleum coke, a carbonaceous material with a high degree of graphitization, through a molten salt electrolytic graphitization method. Compared with traditional graphitization methods, the use of an electrochemical method can effectively reduce the graphitization temperature, thereby reducing the energy consumption and cost of graphitization. Specifically, in step S1, the calcined petroleum coke is subjected to a pelletizing treatment, which can effectively improve the structural stability of the calcined petroleum coke and the conductivity between the calcined petroleum coke and the electrolyte molten salt. Among them, the pelletizing treatment is to make the raw material into a spherical material with a certain shape and strength. In step S2, during the electrolysis process, the molten salt can not only transmit current and provide an environment for the electrolytic reaction, but also promote the orderly arrangement of carbon atoms in the calcined petroleum coke and the formation of a graphite structure through its unique ionic effect and chemical properties. Specifically, the molten salt electrolysis method can not only effectively remove gas element impurities (such as oxygen, sulfur and nitrogen, etc.) in the petroleum coke cathode, but also effectively remove a large amount of sulfur content in the petroleum coke cathode, and at the same time make the removed sulfur ions form sulfur on the surface of the anode, thereby realizing efficient recycling of sulfur resources and reducing the consumption of the anode. In addition, the processing method of the present application has low requirements on the quality of raw materials and is environmentally friendly.

[0022] In one embodiment of the present application, the calcined petroleum coke comprises, by mass percentage: 90-93% carbon, 0.5-1% oxygen, 1-4% sulfur, 0.5-1% nitrogen, and the remainder other impurity elements; and / or the degree of graphitization of the graphitized petroleum coke is 40-65%, preferably 52-65%, and further preferably 55.3-64.8%.

[0023] Calcined petroleum coke refers to the main raw material for making carbon electrodes for aluminum electrolysis in the aluminum electrolysis industry. It is usually obtained by separating light and heavy oils from crude oil through distillation and then converting them into heavy oil through thermal cracking.

[0024] The calcined petroleum coke preferably includes the above elements, which helps to better perform molten salt electrolysis, thereby increasing the degree of graphitization to within the above range.

[0025] In one embodiment of the present application, the above-mentioned step S1 also includes: step S11, grinding the calcined petroleum coke to obtain petroleum coke powder; step S12, pelletizing the petroleum coke powder by spray drying to obtain petroleum coke microspheres; and step S13, wrapping the petroleum coke microspheres with a current collector to obtain a petroleum coke cathode.

[0026] Preferably, the calcined petroleum coke is ground to increase the contact area between the calcined petroleum coke and the electrolyte, thereby improving the subsequent balling process. Preferably, the petroleum coke powder is spray-dried to form a ball, which helps to further improve the structural stability of the calcined petroleum coke and the contact area between the calcined petroleum coke and the electrolyte, thereby improving the conductivity between the electrolyte. Preferably, the petroleum coke microspheres are wrapped with a current collector, which helps to enhance the conductive connection between the petroleum coke microspheres, thereby further reducing the cell pressure.

[0027] In one embodiment of the present application, the particle size of the petroleum coke powder is 1~100nm; and / or the diameter of the spray drying droplets is 20~100μm, and / or the spray drying time is 5~10s; and / or the diameter of the petroleum coke microspheres is 5~10μm; the current collector is selected from any one or more of metal mesh, metal foam, graphite paper, graphite mesh and graphite column.

[0028] The particle size of the petroleum coke powder is preferably within the above range, which helps to enhance its contact area with the electrolyte and the reaction activity. The droplet diameter and time of spray drying and the diameter of the petroleum coke microspheres are preferably within the above range, which helps the petroleum coke microspheres have a good specific surface area and pore structure, thereby facilitating the diffusion of reactants and the release of products. The type of current collector is preferably within the above range, which helps to better perform molten salt electrolysis.

[0029] In order to improve the conductivity of the electrolyte and reduce the temperature of molten salt electrolysis, in one embodiment of the present application, the above step S2 also includes removing moisture from the molten salt and pre-electrolyzing it in sequence to obtain treated molten salt.

[0030] In one embodiment of the present application, the molten salt is evacuated to remove moisture at 180-240° C. in a vacuum environment, and the evacuation time is 16-48 hours.

[0031] It is preferred that the above-mentioned vacuuming method and the vacuuming time be within the above-mentioned range, which helps to effectively remove moisture from the molten salt.

[0032] In one embodiment of the present application, the molten salt is pre-electrolyzed after the water is removed after the temperature is raised to 900-950° C. in an argon atmosphere; and / or the pre-electrolysis voltage is 1.5-2V, and / or the pre-electrolysis time is 1.5-3h.

[0033] It is preferred to increase the temperature before pre-electrolysis and control the voltage and time of pre-electrolysis within the above ranges, which helps to remove impurities in the molten salt, thereby helping to provide an electrolysis environment that is more favorable for graphitization.

[0034] In one embodiment of the present application, the molten salt is selected from eutectic molten salt and / or fluoride, the eutectic molten salt is selected from any one or more of CaCl2-LiCl, CaCl2-NaCl, CaCl2-BaCl2 and CaCl2-KCl, and the fluoride is selected from any one or more of NaF, CaF2, BaF2 and KF.

[0035] The above-mentioned molten salt is preferred because it is easily soluble in water and its electrolysis product is easier to remove, thereby facilitating the acquisition of graphitized petroleum coke with higher purity.

[0036] In one embodiment of the present application, the above-mentioned step S2 also includes: step S21, placing the cathode and anode of the petroleum coke in the treated molten salt in an inert atmosphere for molten salt electrolysis to obtain electrolyzed petroleum coke; and step S22, washing, acid washing and drying the electrolyzed petroleum coke in sequence to obtain graphitized petroleum coke.

[0037] Preferably, the cathode and anode of petroleum coke are placed in the treated molten salt for molten salt electrolysis. The treated molten salt helps to transfer current and provide an environment for electrolysis reaction, thereby promoting the orderly arrangement of carbon atoms in the petroleum coke cathode and the formation of graphite structure. In addition, the treated molten salt is used continuously, and there is no need to replace new electrolytes each time, which helps to reduce costs. Preferably, the electrolytic petroleum coke is washed with water and acid, which helps to remove impurities in the electrolytic petroleum coke, thereby improving the purity of graphitized petroleum coke.

[0038] In one embodiment of the present application, the inert atmosphere is argon or nitrogen; and / or, the anode is graphite; and / or, the temperature of molten salt electrolysis is 850~980°C, and / or, the voltage of molten salt electrolysis is 2.6~3.1V, and / or, the time of molten salt electrolysis is 2~10h; and / or, ultrasonic-assisted distilled water is used for water washing; and / or, acid solution is used for pickling, and the acid solution is a hydrochloric acid solution with a mass concentration of 1~10%; and / or, the drying temperature is 70~80°C.

[0039] The temperature, voltage and time of molten salt electrolysis are preferably controlled within the above ranges, which helps to promote the orderly arrangement of carbon atoms and the formation of graphite structure in the petroleum coke cathode, thereby improving the graphitization degree of the graphitized petroleum coke. It is preferred to use ultrasonic assisted distilled water for water washing, which helps to better remove molten salt and other impurities. It is preferred to use the above acid solution for pickling, which helps to remove metal ion contamination in the petroleum coke after electrolysis. It is preferred to dry under vacuum, and control the drying temperature within the above range, which helps to reduce the structural changes of the graphitized petroleum coke material caused by high temperature.

[0040] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0041] Example 1

[0042] In terms of mass percentage, calcined petroleum coke includes: 92% carbon, 0.8% oxygen, 2.5% sulfur, 0.6% nitrogen, and the rest are other impurity elements. The calcined petroleum coke is ground to obtain a petroleum coke powder with a particle size of 45nm. The petroleum coke powder is pelletized using spray drying to obtain petroleum coke microspheres with a diameter of 8μm, which are then wrapped with a graphite paper current collector to obtain a petroleum coke cathode. The spray drying droplet diameter is 60μm and the spray drying time is 8s.

[0043] 180g of anhydrous CaCl2-LiCl eutectic molten salt (the molar ratio of CaCl2 to LiCl is 0.65:0.35) was placed in an alumina crucible, and the water was removed by vacuum at 200°C for 24h. After heating to 920°C in an argon atmosphere, a pre-electrolysis at 1.8V was performed for 2h to obtain the treated molten salt. In an argon atmosphere, the petroleum coke cathode and graphite anode were placed in the treated molten salt, and a constant voltage 2.8V molten salt electrolysis was performed at 950°C for 6h to obtain electrolyzed petroleum coke. The electrolyzed petroleum coke was washed with ultrasonic-assisted distilled water, acid-washed with a hydrochloric acid solution with a mass concentration of 3%, and dried at 75°C in a vacuum to obtain graphitized petroleum coke.

[0044] Example 2

[0045] In terms of mass percentage, calcined petroleum coke includes: 90% carbon, 0.5% oxygen, 1% sulfur, 0.5% nitrogen, and the rest other impurity elements. The calcined petroleum coke is ground to obtain a petroleum coke powder with a particle size of 1nm. The petroleum coke powder is pelletized using spray drying to obtain petroleum coke microspheres with a diameter of 5μm, which are then placed in a φ8mm graphite frame current collector and connected to a 304 stainless steel rod to form a petroleum coke cathode. The spray-dried droplet diameter is 20μm and the spray drying time is 5s.

[0046] 150g of anhydrous CaCl2-NaCl eutectic molten salt (the molar ratio of CaCl2 to NaCl is 0.7:0.3) was placed in an alumina crucible, and the water was removed by vacuum at 180°C for 48h. After heating to 900°C in an argon atmosphere, a pre-electrolysis at 1.5V was performed for 3h to obtain the treated molten salt. In an argon atmosphere, the petroleum coke cathode and graphite anode were placed in the treated molten salt, and a constant voltage 2.6V molten salt electrolysis was performed at 850°C for 10h to obtain electrolyzed petroleum coke. The electrolyzed petroleum coke was washed with ultrasonic-assisted distilled water, acid-washed with a hydrochloric acid solution with a mass concentration of 1%, and dried at 70°C in a vacuum to obtain graphitized petroleum coke.

[0047] Example 3

[0048] In terms of mass percentage, calcined petroleum coke includes: 93% carbon, 1% oxygen, 4% sulfur, 1% nitrogen, and the rest are other impurity elements. The calcined petroleum coke is ground to obtain a petroleum coke powder with a particle size of 100nm. The petroleum coke powder is pelletized by spray drying to obtain petroleum coke microspheres with a diameter of 10μm, which are then placed in a φ8mm graphite frame current collector and connected to a 304 stainless steel rod to make a petroleum coke cathode. Among them, the spray drying droplet diameter is 100μm, and the spray drying time is 10s.

[0049] 200gBaF2 was placed in an alumina crucible, and the crucible was evacuated at 240℃ and vacuum for 16h to remove moisture. After heating to 950℃ in an argon atmosphere, a 2V pre-electrolysis was performed for 1.5h to obtain the treated molten salt. In an argon atmosphere, the petroleum coke cathode and graphite anode were placed in the treated molten salt, and a constant voltage 3.1V molten salt electrolysis was performed at 980℃ for 2h to obtain electrolyzed petroleum coke. The electrolyzed petroleum coke was washed with ultrasonic-assisted distilled water, acid-washed with a hydrochloric acid solution with a mass concentration of 10%, and dried at 80℃ in a vacuum to obtain graphitized petroleum coke.

[0050] Example 4

[0051] The difference from Example 1 is that the diameter of the spray-drying droplets is 100 μm, the spray-drying time is 10 s, and graphitized petroleum coke is finally obtained.

[0052] Example 5

[0053] The difference from Example 1 is that the diameter of the spray-drying droplets is 150 μm, the spray-drying time is 3 s, and graphitized petroleum coke is finally obtained.

[0054] Example 6

[0055] The difference from Example 1 is that the temperature of molten salt electrolysis is 980° C., and graphitized petroleum coke is finally obtained.

[0056] Example 7

[0057] The difference from Example 1 is that the temperature of molten salt electrolysis is 820° C., and graphitized petroleum coke is finally obtained.

[0058] Example 8

[0059] The difference from Example 1 is that the voltage of molten salt electrolysis is 2.6 V, the time of molten salt electrolysis is 4 h, and graphitized petroleum coke is finally obtained.

[0060] Example 9

[0061] The difference from Example 1 is that the voltage of molten salt electrolysis is 3.5 V, the time of molten salt electrolysis is 1 hour, and graphitized petroleum coke is finally obtained.

[0062] Comparative Example 1

[0063] The calcined petroleum coke was placed in an Acheson graphitization furnace and heated at 3000°C for 48 hours to obtain graphitized petroleum coke.

[0064] Comparative Example 2

[0065] The difference from Example 1 is that after the calcined petroleum coke is ground, it is wrapped with a graphite paper current collector to obtain a petroleum coke cathode, and finally graphitized petroleum coke is obtained.

[0066] Test Method

[0067] The performance of the graphitized petroleum cokes of the above examples and comparative examples was tested, and the test results are shown in Table 1.

[0068] Table 1

[0069]

[0070] in, Figure 1 is the XRD pattern of graphitized petroleum coke in Example 1. Figure 1 It can be seen that the diffraction angle corresponding to the (002) crystal plane of the calcined petroleum coke after molten salt electrolysis is 26.33°. According to the graphitization degree calculation formula Mering-Maire (Franklin formula), under the electrolysis conditions, the graphitization degree of the calcined petroleum coke is 64.2%.

[0071] Compared with the high-temperature graphitization method of comparative example 1, the embodiment of the present application can still achieve a higher degree of graphitization at a lower temperature. Therefore, the present application can reduce the energy consumption and cost of graphitization of calcined petroleum coke while taking into account the degree of graphitization of graphitized petroleum coke.

[0072] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0073] The present application converts low-graphitization calcined petroleum coke into graphitized petroleum coke, a carbonaceous material with a high degree of graphitization, through a molten salt electrolytic graphitization method. Compared with traditional graphitization methods, the use of an electrochemical method can effectively reduce the graphitization temperature, thereby reducing the energy consumption and cost of graphitization. Specifically, in step S1, the calcined petroleum coke is subjected to a pelletizing treatment, which can effectively improve the structural stability of the calcined petroleum coke and the conductivity between the calcined petroleum coke and the electrolyte molten salt. Among them, the pelletizing treatment is to make the raw material into a spherical material with a certain shape and strength. In step S2, during the electrolysis process, the molten salt can not only transmit current and provide an environment for the electrolytic reaction, but also promote the orderly arrangement of carbon atoms in the calcined petroleum coke and the formation of a graphite structure through its unique ionic effect and chemical properties. Specifically, the molten salt electrolysis method can not only effectively remove gas element impurities (such as oxygen, sulfur and nitrogen, etc.) in the petroleum coke cathode, but also effectively remove a large amount of sulfur content in the petroleum coke cathode, and at the same time make the removed sulfur ions form sulfur on the surface of the anode, thereby realizing efficient recycling of sulfur resources and reducing the consumption of the anode. In addition, the processing method of the present application has low requirements on the quality of raw materials and is environmentally friendly.

[0074] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for graphitizing calcined petroleum coke, wherein the calcined petroleum coke is obtained from crude oil by distillation and thermal cracking, characterized in that: The graphitization treatment method comprises: Step S1, pelletizing the calcined petroleum coke to obtain a petroleum coke cathode; and Step S2, subjecting the petroleum coke cathode and anode to molten salt electrolysis to obtain graphitized petroleum coke.

2. The graphitization method according to claim 1, characterized in that: In terms of mass percentage, the calcined petroleum coke comprises: 90-93% carbon, 0.5-1% oxygen, 1-4% sulfur, 0.5-1% nitrogen, and the remainder is other impurity elements; and / or the graphitization degree of the graphitized petroleum coke is 40-65%.

3. The graphitization method according to claim 1 or 2, characterized in that: The step S1 further comprises: Step S11, grinding the calcined petroleum coke to obtain petroleum coke powder; Step S12, performing the ball-forming treatment on the petroleum coke powder by spray drying to obtain petroleum coke microspheres; and Step S13, using a current collector to wrap the petroleum coke microspheres to obtain the petroleum coke cathode.

4. The graphitization method according to claim 3, characterized in that: The particle size of the petroleum coke powder is 1-100 nm; and / or the diameter of the spray-dried droplets is 20-100 μm, and / or the spray-drying time is 5-10 s; and / or the diameter of the petroleum coke microspheres is 5-10 μm; the current collector is selected from any one or more of metal mesh, metal foam, graphite paper, graphite mesh and graphite column.

5. The graphitization method according to claim 1 or 2, characterized in that: The step S2 also includes removing moisture from the molten salt and pre-electrolyzing the molten salt in sequence to obtain treated molten salt.

6. The graphitization method according to claim 5, characterized in that: The molten salt is vacuumed at 180-240° C. to remove moisture, and the vacuuming time is 16-48 hours.

7. The graphitization method according to claim 5, characterized in that: The pre-electrolysis is performed on the molten salt after the water is removed after the temperature is raised to 900-950° C. in an argon atmosphere; and / or the voltage of the pre-electrolysis is 1.5-2V, and / or the time of the pre-electrolysis is 1.5-3h.

8. The graphitization method according to claim 5, characterized in that: The molten salt is selected from eutectic molten salt and / or fluoride, the eutectic molten salt is selected from any one or more of CaCl2-LiCl, CaCl2-NaCl, CaCl2-BaCl2 and CaCl2-KCl, and the fluoride is selected from any one or more of NaF, CaF2, BaF2 and KF.

9. The graphitization method according to claim 5, characterized in that: The step S2 further comprises: Step S21, placing the petroleum coke cathode and the anode in the treated molten salt in an inert atmosphere to perform molten salt electrolysis to obtain electrolyzed petroleum coke; and Step S22, washing, acid washing and drying the electrolyzed petroleum coke in sequence to obtain the graphitized petroleum coke.

10. The graphitization method according to claim 9, characterized in that: The inert atmosphere is argon or nitrogen; and / or the anode is graphite; and / or the temperature of the molten salt electrolysis is 850-980° C., and / or the voltage of the molten salt electrolysis is 2.6-3.1 V, and / or the time of the molten salt electrolysis is 2-10 h; and / or, using ultrasonic wave-assisted distilled water for the water washing; And / or, the pickling is performed using an acid solution, wherein the acid solution is a hydrochloric acid solution with a mass concentration of 1-10%; and / or, the drying temperature is 70-80°C.

Citation Information

Patent Citations

  • Electrochemical desulfurization method for petroleum coke

    CN111349503A

  • Artificial graphite negative electrode active material and preparation and application thereof

    CN115611275A

  • Fast charging graphite and preparation method thereof, negative plate and battery

    CN116588923A